Exergy analysis on solar thermal systems: A better understanding of their sustainability - Kalogirou, Soteris A.; Karellas, Sotiriοs; Badescu, Viorel; Braimakis, Konstantinos (My University, 2016)
This paper presents a review of exergy analysis of solar thermal systems. It includes both various types of solar collectors and various applications of solar thermal systems. As solar collectors are an important technology when sustainability is considered, exergy analysis, which gives a more representative performance evaluation, is a valuable method to evaluate and compare possible configurations of these systems. It should be noted that this review is based on literature published in the last two years.
Keywords: Exergy analysis; Sustainability; Solar collectors; Solar processes